ENGLISH ANATOMICAL TERMS BY ORIGIN IN THE TEXTBOOK HUMAN ANATOMY(I-II) - Litevkienė, Nijolė; Korosteliova, Jelena (PROFESSIONAL STUDIES: Theory And Practice, 2023)
This research is aimed to identify the particularities of English anatomical terms, based on comparative description of structural forms and in terms of origin. One-word and compound English and Latin anatomical terms are compared. This research was based on the use of anatomical terms in the textbook “Human Anatomy”, published by M. Prives, V. Bushkovich, N. Lisenkov, who offer a progressive view towards? descriptive, evolutionary, functional, and practical anatomy. Medical terms in the textbook can be basically divided into one-word and multi-word terms. One-word terms can be simple words, derived words, compounds, or a combination of derived and compound words. Compound anatomical terms can consist of two-six words. More than a half of the one-word English anatomical terms are formed on the basis of the English lexis. Most English compound anatomical terms are formed using the terms of Latin or Greek languages.